Measuring EU actorness through CFSP and ESDP:Civilian power EU - (:unkn) unknown (My University, 2009)
Avrupa Birligi (AB) bütünleşme sürecinde dış, güvenlik ve savunma politikaları önceliğini daima koruyacaktır. 1970’lerden bu yana Avrupa Siyasi İşbirliği (ASİ) adı altında başlayan bu alanlardaki işbirliği günümüze kadar bir dönüşüm sürecinden geçmektedir. Günümüzde hararetli tartışmaların ortasında bulunan en önemli gelişme ise ASİ içinden dogan Ortak Dış ve Güvenlik Politikası (ODGP) ile ODGP içinden yaratılan Avrupa Güvenlik ve Savunma Politikası (AGSP) alanlarıdır. Bu gelişmelerin yarattığı bir başka tartışma konusu ise Avrupa’nın ne tür bir güç oldugunun irdelenmesidir. Bu makalede ele alınan konulardan ilki AB’nin aktif bir uluslararası güç olduğu fakat siyasi ve kurumsal bir kimlik oluşturamadığı sorunudur. Bugünün küresel dünyasında AB’nin bir sivil güç mü yoksa normatif ya da askeri bir güç olma yolunda ilerleyip ilerlemedigi tartışılmaktadır. Bu nedenle makalenin ikinci tartışma noktası AB’nin ne tür bir güç oldugu sorusunun irdelenmesi ve AB’nin giderek güçlenen bu nüfuzunun sivil ve askeri yeteneklerinin irdelenmesiyle ölçülebileceğidir.

The European Union Foreign Security and Defense policies have always been a strategic issue for the Union. The Union has been debating on these policies since the beginning of the 70’s which is the period of time coincides with the introduction of the European Political Coorperation (EPC) Today the discussion mostly centers on the Common Foreign and Security Policy (CFSP) which is the successor of EPC, and the European Security and Defense Policy (ESDP) which was in fact derived from the CFSP itself. There are two main points of debate behind these discussions. The first is whether the Union has the capability and strength to act in a civilian, normative or military capacity. The second question is will both the CFSP and ESDP be successful enough to assert the strength of the EU on the international stage. The main discussion within this paper assumes that the EU is in fact an active force, although it manifests some shortcomings which are that the EU lacks a clear and stable political and institutional identity. To address the second point of debate, this article focuses on how the EU might be evaluated (as a civilian, normative or military power) with its increasing powers in today’s globalizing world. The only way of quantifying the Union’s increase in power is through the detailed analysis of its civilian and military capabilities.
Keywords: Uluslararası İlişkiler; Siyasi Bilimler